PERAN PRIVATE MILITARY COMPANY (PMC) DALAM KONFLIK KRISIS KEPRESIDENAN VENEZUELA 2018-2020 - Mulyadi, Ahmad; Aisha, Nina Widyaswasti; Prabowo, Ramiro (Moestopo Journal of International Relations (MJIR), 2024)
This research aims to analyze The Role of Private Military Companies (PMC) in Conflict Venezuelan Presidential Crisis 2018-2020. The research method used is a descriptive research method with a qualitative approach, where data collection is carried out through book sources, journal articles, essays, theses, and also internet sites. This research uses the theory of hard power diplomacy, where hard power diplomacy is a "tool" or approach in international relations that uses military and economic power to influence or force another party or country to follow the policies or interests of the country concerned. This often involves the use of threats, sanctions, economic pressure, or military action to achieve political goals. In this case, it can be seen that the US used hard power diplomacy, where the US used all its means to overthrow President Maduro by giving various "sanctions" to the country of Venezuela and supporting a puppet leader, who at that time wanted to become President Maduro's replacement.